Evaluation of safety and efficacy of Unani Add-on regimen in preventing the progression of severity of the disease in hospitalized SARS-CoV2 tested positive asymptomatic /mild to moderate symptomatic COVID-19 cases- A Randomised Controlled Clinical Trial (Bangladesh Journal of Medical Science, 2022)
Objectives: The study aimed to establish the effectiveness of Unani add-on regimen by comparing theduration required for change in disease status from COVID-19 positive asymptomatic / mildto moderate symptomatic patients to asymptomatic negative.Methods: This single-centric, randomized, twin arm, controlled, clinical trial was carried out on a totalnumber of 62 RT-PCR confirmed COVID-19 patients. The Intervention group (IG) receivedUnani Regimen (Khameera Marwareed and Unani Joshanda) in addition to the conventional management, while the Control group (CG) received only conventional management.Results: It was observed that 16 (51.6%) patients in Intervention Group and 3 (9.4%) patients incontrol group became negative for COVID-19 at day 7 and remaining 13 out of 15 (93.5%) patients in Intervention Group and 20 out of 28 (74.1%) patients in control group becamenegative for COVID-19 at day 14 .This effect of the Unani Regimen in comparison to thecontrol group was statistically significant (p =0.003).Conclusions: It can be concluded that the change of COVID-19 positive asymptomatic / mild to moderate symptomatic patients to RT-PCR negative was much earlier in the add-on Unani regimen group as compared to control group.Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 901-911